A molecular dynamics study of nano-encapsulated phase change material slurry. (5th April 2016) - Wang, Yan; Chen, Zhenqian; Ling, Xiang
Highlights: A molecular dynamics study of octadecane melting is proposed. Octadecane–water slurry simulations were performed to study the melting mechanism. It revealed the relationship between heat capacity and octadecane mass fraction. Abstract: Phase change material, which holds a good promise as a media of thermal energy storage, attracts more and more interest in the past decade. In this context, a classic all atom molecular dynamics approach was applied to investigate the thermodynamic properties of crystalline octadecane and octadecane–water slurry. The octadecane structure was established and heated up to study the melting behavior. The relationship between octadecane potential energy change and temperature was presented to determine the melting point. Heat capacity was evaluated to better understand the performance of energy storage system. We also performed the octadecane slurry simulations. The results suggested that the potential energy change of the slurry had a good agreement with lantern heat of octadecane. The pure water simulation was carried out to make a reference for octadecane–water slurry. It has been found that the heat capacity of octadecane slurry decreases with octadecane mass fraction increase. However, with heat absorbed during phase change, the slurry would provide larger heat capacity, which is beneficial to thermal energy storage system.